Polymorphism in genes encoding two fatty acid binding proteins increases risk of ischemic stroke in a Chinese Han population - Cao, Maolin; Zhang, Yifei; Chen, Dan; Zhong, Jiaju; Zhang, Xiaoli; Yang, Ling; Li, Xue; Fang, Liang; Liu, Beizhong; Gong, Fang; Zhou, Chanjuan (Frontiers in Genetics, 2023)
Background: Dyslipidemia is an independent predictor of ischemic stroke (IS). Genetic variations in lipid-metabolism related genes may increase the risk of IS. Fatty acid-binding protein 1 (FABP1) and fatty acid-binding protein 2 (FABP2) are lipid chaperones responsible for lipid transport and metabolism. The present study aimed to determine the association between FABP1 or FABP2 and ischemic stroke. Methods: A total of 251 participants were recruited composed of 138 patients with ischemic stroke and 113 healthy subjects. DNA was extracted from peripheral blood samples. The rs2241883 polymorphism in FABP1 and rs1799883 polymorphism in FABP2 were genotyped using polymerase chain reaction-restriction fragment length polymorphism. Generalized multifactor dimensionality reduction (GMDR) was used to find out the interaction combinations between two SNPs and environmental factors. Results: The GA genotype of FABP2 rs1799883 increased susceptibility to ischemic stroke under overdominant inheritance model (P = 0.042). After adjusting for the risk factors of IS,it was associated with a significantly higher risk of IS in the codominant inheritance model(adjust OR = 3.431, 95%CI = 1.060-11.103, P = 0.04). The interactions of FABP1 rs2241883 and FABP2 rs1799883 were not associated with IS risk (P = 0.172). Moreover, interaction analysis of two genes (rs1799883 and rs2241883) and two environmental factors (smoking and alcohol consumption) was associated with an increased risk of IS (P = 0.011). Conclusion: The GA genotype of FABP2 rs1799883, interactions between rs1799883, rs2241883 and smoking and alcohol consumption were associated with IS risk in Chinese Han populations. Keywords: fatty acid-binding protein 1, fatty acid-binding protein 2, single nucleotide polymorphism, ischemic stroke